Since there is no = sign in that equation, I assumne it should be equal to zero. If that is the case then m= -1/8
2006-11-14 09:39:29
·
answer #1
·
answered by Dana B 2
·
1⤊
0⤋
I don't see an = anywhere. I'll guess it all is =0
5m + 9 + 3(m - 5) + 7=0
5m+3m+9-15+7=0
8m+1=0
m=-1/8
2006-11-14 09:42:17
·
answer #2
·
answered by yupchagee 7
·
0⤊
0⤋
If you meant this...
5m + 9 = 3(m - 5) + 7
then...
5m + 9 = 3m - 15 + 7
2m + 9 = -8
2m = -17
m = -17/2
2006-11-14 09:37:47
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
5m + 9 + 3(m-5) + 7
5m + 9 + 3m - 15 + 7
8m + 9 - 15 + 7
8m + 1
That's all the farther you can go.
2006-11-14 09:41:27
·
answer #4
·
answered by He Haunts Me 2
·
0⤊
0⤋
There is no equal sign in this equation so there is no way to solve it, but if there was- first do the distrubive property to get rid of the parenthesis, then combine like terms, then undo the addition, then undo the multiplication.
2006-11-14 09:41:10
·
answer #5
·
answered by smartypants909 7
·
0⤊
0⤋
is it m= -1/8
2006-11-14 09:39:16
·
answer #6
·
answered by llp_pl 2
·
0⤊
0⤋
it has to equal to something, and it doesn't
2006-11-14 09:37:48
·
answer #7
·
answered by Suey 2
·
0⤊
0⤋